ANALISIS ISI PESAN PADA PROGRAM TALKSHOW KICK ANDY DI METRO TV EDISI JULI 2018 (SERI ANAK MUDA BERPRESTASI) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study examines the analysis of message content and the frequency of appearance of message content contained in the July 2018 edition of the Kick Andy program broadcast by the private television station Metro TV. In the discussion, several problem formulations were compiled, namely: What was the dominant message in the July 2018 edition of the Kick Andy Talkshow program on Metro TV? What are the factors that support the application of message orientation in the July 2018 edition of the Kick Andy Talkshow program on Metro TV? The results showed that the appearance of the message content with the most dominant frequency appeared through the function of the message content containing informative messages, namely as many as thirty-four messages (40.47%). Then in the second-order, the function of the message content contains motivational messages as many as thirty-three messages (39.28%). In the last sequence, namely the message content function containing socialization messages as many as seventeen messages (20.23%). The factors that support the application of message orientation in the July 2018 edition of the Kick Andy Talkshow program on Metro TV, namely, using communicative language, discussing material relevant to contemporary reality, presented with interesting and relevant back sounds and images and advertisements displayed after the material is finished.